Common Force Field Thermodynamics of Cholesterol. (5th November 2013) - Giangreco, Francesco; Yamamoto, Eiji; Hirano, Yoshinori; Hodoscek, Milan; Knecht, Volker; di Giosia, Matteo; Calvaresi, Matteo; Zerbetto, Francesco; Yasuoka, Kenji; Narumi, Tetsu; Yasui, Masato; Höfinger, Siegfried
Abstract : Four different force fields are examined for dynamic characteristics using cholesterol as a case study. The extent to which various types of internal degrees of freedom become thermodynamically relevant is evaluated by means of principal component analysis. More complex degrees of freedom (angle bending, dihedral rotations) show a trend towards force field independence. Moreover, charge assignments for membrane-embedded compounds are revealed to be critical with significant impact on biological reasoning.